A novel thin film composite hollow fiber osmotic membrane with one-step prepared dual-layer substrate for sludge thickening - Ng, Daniel Yee Fan (2020)
Forward osmosis (FO) membranes have received attention as an energy-efficient and low-cost technique in stream concentrating processes. In this work, a novel double-skinned hollow fiber thin film composite (TFC) FO membrane has been successfully fabricated, which consists of a one-step prepared dual layer substrate and a thin inner selective layer formed via interfacial polymerization. The substrate consists of a relatively dense ultrafiltration (UF) outer layer and a porous UF inner layer, both of which were constructed from polyethersulfone (PES) as the substrate material by using dual-layer co-extrusion technique. Compared to the commercial and reported double-skinned FO membranes, the FO membrane developed in this work exhibited a higher permeate flux with humic acid solution as feed. Furthermore, the double-skinned FO membrane was applied in concentrating activated sludge using 0.5 M NaCl as draw solution, and a permeate flux at 5.4 L/m2h was achieved after 5 h operation, which was higher than or comparable to those of the reported FO membranes. Membrane autopsies and foulant analysis suggested that the dense UF skin layer helped to reject greater-sized organic foulants (> 300 Da). This study shed light on the important fabrication features and promising application of the double-skinned hollow fiber TFC FO membrane in sludge concentration.